Musical Leisure Activities in Elementary School Students: The Role of Music-Related Beliefs, Sex, Socioeconomic Status, and Migration Background - Penthin, Marcus; Birnbaum, Lisa; Fritzsche, Eva; Kröner, Stephan (SAGE Open, 2025)
The present study aims to investigate the effects of music-related beliefs on musical leisure activities of elementary school students. To this end, the relationship between music-related beliefs and musical leisure activities was examined while controlling for sex, socio-economic status, and migration background. Data analyses are based on a survey-based study conducted with n = 685 fourth-graders in Germany. Sex and socioeconomic status, but not migration background, explained a small amount of variance in musical leisure activities. After including the music-related beliefs as predictors, they completely mediated the effects of domain-general variables on musical leisure activities and explained 77% of variance in musical leisure activities, with all predictors except the intrinsic value showing unique effects. This work further contributes to the development of reliable and valid scales for the assessment of music-related beliefs. When considering avenues for further research, we emphasize that it is important to incorporate a broad range of music-related beliefs as determinants of leisure musicking in childre
Keywords: beliefs; elementary school children; extracurricular activities; leisure-time activities; musical self-concept; musicking